Motivasi Warga Belajar dalam Mengikuti Program Pendidikan Kesetaraan Paket C SKB Gudo Jombang - Nabilla, Agustin Khanza; Nusantara, Widya (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan UNESA, 2024)
The aims of this research are (1) To find out and describe students' motivation in participating in the package C equality education program at SKB Gudo, (2) To describe the factors that influence students in participating in the package C equality education program at SKB Gudo Jombang. This research use desciptive qualitative approach. Data collection was carried out through observation, interviews and documentation. The data analysis carried out was data collection, data reduction, data presentation and drawing conclusions. Data validity is carried out by credibility, transferability, dependability and confirmability. The results obtained in this research are: (1) The motivation for students to take package C at SKB Gudo Jombang is the role of parents, the role of tutors, and the role of the social environment. (2) Factors that influence the motivation of residents to take part in the equivalent education package C SKB Gudo Jombang are the self-awareness of people studying from different backgrounds, namely economic factors, dropping out of school, bullying or bullying and the desire to take part in equal education. Work